Hegelian Phenomenology of Spirit and Boxing Fight - Kosiewicz Jerzy (Sciendo, 2018)
In the presented text the author points out to anthropological as well as axiological foundations of the boxing fight from the viewpoint of Hegel's philosophy. In the genial idealist's views it is possible to perceive the appreciation of the body, which constitutes a necessary basis for the man's physical activity, for his work oriented towards the self-transformation and the transformation of the external world, as well as for rivalry and the hand-to-hand fight. While focusing our attention on the issue of rivalry and on the situation of the fight - and regarding it from the viewpoint of the master - slave theory (included in the phenomenology of spirit), it is possible to proclaim that even a conventionalised boxing fight - that is, restricted by cultural and sports rules of the game - has features of the fight to the death between two Hegelian forms of selfknowledge striving for self-affirmation and self-realisation. In the boxing fight, similarly as in the above mentioned Hegelian theory, a problem of work and of the development of the human individual (that is, of the subject, self-knowledge, the participant of the fight) appears. There appears also a prospect of death as a possible end of merciless rivalry. The fight revalues the human way in an important way, whereas the prospect for death, the awareness of its proximity, the feeling that its close and possible, saturates the life with additional values. It places the boxer, just like every subject fighting in a similar or a different way, on the path towards absolute abstraction - that is, it brings him closer to his self-fulfilment in the Absolute, to the absolute synthesis. The Hegelian viewpoint enables also to appreciate the boxing fight as a manifestation of low culture (being in contrast with high culture), to turn attention to the relations which - according to Hegel - take place between the Absolute and the man, as well as to show which place is occupied by the subject both in the process of the Absolute's self-realisation and in the German thinker's philosophical system. Independently of the dialectical, simultaneously pessimistic and optimistic overtone of considerations connected with the very boxing fight (regarding destruction and spiritualisation on a higher level), it is possible to perceive farreaching appreciation of the human individual in Hegel's philosophy since the Absolute cannot make its own self-affirmation without the individual, without the human body, without the fight aimed at the destruction of the enemy and without the subjective consciousness and the collective consciousness which appear thanks to this fight. Thus, it is justified to suppose that the foundation of the whole Hegel's philosophy is constituted by anthropology and that in the framework of this anthropology a special role is played by the fight and by work, which changes the subject and his(her) environment. Admittedly Hegel does not emphasise it explicitly, nevertheless his views (with their centre, which, according to Hegel himself and his interpreters, is constituted by the Absolute) have, as a matter of fact, an anthropocentric character and the main source of the subject's development is the struggle which, irrespectively of its result, always primarily leads to the destruction or even to the death of one of the sides, just like in the boxing fight. However, it is also a germ of the positive re-orientation of the subject, the beginning and a continuation of that what the phenomenology of the spirit describes as a movement towards absolute abstraction.